Catastrophizing in Patients with Burning Mouth Syndrome - Ana ANDABAK ROGULJ; Ivica Richter; Vlaho Brailo; Igor Krstevski; Vanja VUČIĆEVIĆ BORAS (University of Zagreb. School of Dental Medicine, 2014)
Background: Burning mouth syndrome (BMS) is an idiopathic painful condition which manifests with burning sensations in the oral cavity in patients with clinically normal oral mucosa and without any local and/or systemic causative factor. Catastrophizing is defined as an exaggerated negative orientation toward pain stimuli and pain experience. The aim of this study was to examine the association between catastrophizing and clinical parameters of BMS, and to examine the association between catastrophizing and the quality of life in patients with BMS. Materials and methods: Anonymous questionnaire consisting of 3 parts (demographic and clinical data with 100 mm visual analogue scale (VAS), Croatian version of the Oral Health Impact Profile (OHIP-14) scale and Croatian version of the Pain Catastrophizing scale (PC), was distributed to 30 patients diagnosed with BMS. Results: A higher level of catastrophizing was clinically significant in 30% of the patients. Total catastrophizing score and all three subcomponents of catastrophizing significantly correlated with the intensity of symptoms, but did not correlate with the duration of symptoms. Gender and previous treatment did not affect the catastrophizing. Conclusion: Obtaining the information about catastrophizing could help a clinician to identify patients with negative behavioural patterns. Additional psychological intervention in these individuals could reduce/eliminate negative cognitive factors and improve coping with chronic painful condition such as BMS.